Decolonization and the cold war : negotiating independence - James, Leslie, 1980-; Leake, Elisabeth (London : Bloomsbury, 2015)
"The Cold War and decolonization transformed the twentieth century world. This volume brings together an international line-up of experts to explore how these transformations took place and expand on some of the latest threads of analysis to help inform our understanding of the links between the two phenomena. The book begins by exploring ideas of modernity, development, and economics as Cold War and postcolonial projects and goes on to look at the era's intellectual history and investigate how emerging forms of identity fought for supremacy. Finally, the contributors question ideas of sovereignty and state control that move beyond traditional Cold War narratives. Decolonization and the Cold War emphasizes new approaches by drawing on various methodologies, regions, themes, and interdisciplinary work, to shed new light on two topics that are increasingly important to historians of the twentieth century"--
Includes bibliographical references and index.
Keywords: World politics -- 1945-1989.; Cold War; Decolonization -- History -- 20th century